The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/gox.0000000000004623
|View full text |Cite
|
Sign up to set email alerts
|

Using Closed Incision Negative Pressure Therapy Specialty Dressings over Incisions following Sternal Dehiscence Reconstruction

Abstract: Background: Surgical site complications (SSCs) after median sternotomy, such as deep sternal wound infection and sternal dehiscence, are rare but can be catastrophic. If undetected, there is an elevated risk of mortality. Reconstructive surgery consisting of debridement, sternectomy, and muscle flap coverage is widely used as standard of care for deep sternal wound infection. Methods: This was an observational, retrospective cohort study of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Negative pressure wound therapy (NPWT) is a relatively new treatment strategy. Owing to its excellent wound healing effect, it is used to treat a wide range of conditions, 1 , 2 such as traumatic wounds, 3 pressure sores, open abdomens, sternal wounds, 4 diabetic foot, 5 second-degree burns, skin flaps, 6 and skin graft recipient sites. 7 However, no study has examined and reported on treating fingertip infection–associated soft tissue defects using NPWT.…”
Section: Introductionmentioning
confidence: 99%
“…Negative pressure wound therapy (NPWT) is a relatively new treatment strategy. Owing to its excellent wound healing effect, it is used to treat a wide range of conditions, 1 , 2 such as traumatic wounds, 3 pressure sores, open abdomens, sternal wounds, 4 diabetic foot, 5 second-degree burns, skin flaps, 6 and skin graft recipient sites. 7 However, no study has examined and reported on treating fingertip infection–associated soft tissue defects using NPWT.…”
Section: Introductionmentioning
confidence: 99%